2007
DOI: 10.1038/sj.bjp.0707328
|View full text |Cite
|
Sign up to set email alerts
|

Region‐dependent attenuation of μ opioid receptor‐mediated G‐protein activation in mouse CNS as a function of morphine tolerance

Abstract: Background and purpose: Chronic morphine administration produces tolerance in vivo and attenuation of m opioid receptor (MOR)-mediated G-protein activation measured in vitro, but the relationship between these adaptations is not clear. The present study examined MOR-mediated G-protein activation in the CNS of mice with different levels of morphine tolerance. Experimental approach: Mice were implanted with morphine pellets, with or without supplemental morphine injections, to induce differing levels of toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
6
29
1
Order By: Relevance
“…Receptor desensitization in specific brain regions, including brain stem nuclei, has been previously observed autoradiographically using DAMGO-stimulated [ 35 S]GTPγS in chronic morphine tolerance mouse and rat models (54,55), with similar results in membrane-binding studies from morphine-tolerant mouse brain stem (56). In our study, morphine-tolerant control WT mE7M-B6 mice exhibited reduced morphine-stimulated G protein coupling in the brain stem following chronic morphine treatment, consistent with previous observations.…”
Section: Discussionsupporting
confidence: 80%
“…Receptor desensitization in specific brain regions, including brain stem nuclei, has been previously observed autoradiographically using DAMGO-stimulated [ 35 S]GTPγS in chronic morphine tolerance mouse and rat models (54,55), with similar results in membrane-binding studies from morphine-tolerant mouse brain stem (56). In our study, morphine-tolerant control WT mE7M-B6 mice exhibited reduced morphine-stimulated G protein coupling in the brain stem following chronic morphine treatment, consistent with previous observations.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, these studies demonstrate that OR desensitization is not only agonist-dependent but also neuron-or region-dependent. Furthermore, a recent study by Sim-Selley et al (2007), showed the degree of OR desensitization increases in some brain regions and becomes significant in others when the dose of long-term morphine administration was increased. Although this may be somewhat expected, this study drives home the effect of dose and duration of exposure on the long-term adaptive events that occur after prolonged drug usage across different neuronal populations.…”
Section: Biased Agonism With Respect To Receptor Desensitizationmentioning
confidence: 99%
“…Ultimately, the specific molecular mechanisms governing morphine tolerance have not been fully elucidated, and the possibility that mechanisms of morphine tolerance vary depending on the specific brain and spinal cord region requires further investigation (51).…”
Section: Mu-opioid Receptor-mediated Changesmentioning
confidence: 99%